Variation in essential oil composition of Hypericum scabrum L. and H. scabroides N. Robson & Poulter (Hypericaceae) aerial parts during its phenological cycle - Bagci, Eyup; Bekci, Fatih (Soc Botanique France, 2010)
The quantitative and qualitative variations of the essential oils from the aerial parts of Hypericum scabrum L and H scabroides N Robson & Poulter from Turkey were examined Plant materials were harvested at different phenological stages (i e. vegetative, flowering and fruiting stages) of the life cycle of both Hypericum species Analysis by GC and GC-MS of the essential oils enabled us to identify 67 of the whole components The main components were nonane, alpha-pinene, beta-pinene, beta-myrcene, d-limonene and germacrene-D in H scabrum oil and, as additional, sabinene, delta 3-carene were found as the main constituents in H scabroides However, monoterpenoids composition and partly sesquiterpenoids levels varied with the phenological cycle and the number of compounds detected increased during ontogenesis in particular at fruiting stage in both Hypericum species
Keywords: Hypericum scabrum; H scabroides; Hypericaceae; essential oils; phenological cycle